Exosome miR-199a-5p modulated vascular remodeling and inflammatory infiltration of Takayasu’s arteritis - Guo, Shuning; Li, Jiehan; Pang, Shurui; Li, Jing; Tian, Xinping (Arthritis research & therapy, 2025)
Advances in treatment have swiftly alleviated systemic inflammation of Takayasu's arteritis (TAK), while subclinical vascular inflammation and the ensuing arterial remodeling continue to present unresolved challenges in TAK. The phenotypic switching of vascular smooth muscle cells (VSMC) is regarded as the first step in vascular pathology and contributes to arterial remodeling. Exosomes facilitate the transfer and exchange of proteins and specific nucleic acids, thereby playing a significant role in intercellular communication. Little is known about the modulatory role of serum exosomes in phenotypic switching of VSMC and vascular remodeling in TAK. Serum exosomes isolated from TAK patients were co-cultured with VSMC to identify the modulatory role of exosomes. VSMC were transfected with miR-199a-5p mimic and inhibitor. CCK8 assays and EdU assays were performed to measure proliferative ability. The migration of VSMC was evaluated by scratch assays and transwell migration assays. The flow cytometry was employed to identify apoptosis of VSMC. Dual-luciferase reporter assay, RNA immunoprecipitation assay and fluorescence in situ hybridization were utilized to validate the target gene of miR-199a-5p. The correlational analysis was conducted among exosome miRNA, serum MMP2, TIMP2 and clinical parameters in TAK patients. The coculture of VSMC with serum exosome mediated dedifferentiation of VSMC. Through gain- and loss-of-function approaches, miR-199a-5p over-expression significantly increased expression of VSMC marker genes and inhibited VSMC proliferation and migration, whilst the opposite effect was observed when endogenous miR-199a-5p was knocked down. The overexpression of miR-199a-5p suppressed VSMC apoptosis. Further, MMP2 serves as functional target gene of miR-199a-5p. The correlation analyses revealed an inverse correlation between Vasculitis Damage Index and exosome miR-199a-5p level or serum MMP2, which requires validation in a larger cohort. Our study indicated that the miR-199a-5p/MMP2 pathway played a role in inhibiting the migration, proliferation and apoptosis of VSMC. The decreased secretion of MMP2 may potentially prompt the intimal infiltration of inflammatory cells within the vascular wall, offering a novel therapeutic opportunity by tackling both inflammatory responses and the neointimal overgrowth associated with TAK arterial damage. Moreover, exosome miR-199a-5p and MMP2 derived from serum possess potential as future biomarkers for vascular injury.